Dampak Penggunaan Media Sosial terhadap Moralitas Individu: Analisis Berdasarkan Nilai-Nilai Islam - Nursoiman Nursoiman; Sapto Depiyanto; Deryl Kamudya; Toni Prasetyo; Ismail Mubarok (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
This study examines the shift in individual morality caused by social media use and formulates a digital ethics framework grounded in Islamic values. The rapid growth of social media has transformed patterns of communication, participation, and self-expression, but it has also created moral challenges, including misinformation, cyberbullying, hate speech, and declining modesty in digital interactions. This research employs a qualitative descriptive approach through content analysis of literature related to digital ethics, Islamic law, and online moral behavior. The findings show that structural characteristics of social media, such as anonymity, virality, immediacy, and weak social control, encourage online disinhibition and weaken individual moral self-regulation. However, Islamic values, particularly Tabayyun as information verification, Hifzhul Lisan as control of speech, and Muraqabah as awareness of divine supervision, can function as ethical filters in guiding responsible digital behavior. This study concludes that integrating Islamic moral principles into social media practices is essential to strengthen personal ethics, prevent harmful online conduct, and foster a more civilized digital culture among diverse users in contemporary online society.